The maze at Windermere : a novel - Smith, Gregory Blake (New York : Viking, 2018)
"A richly layered novel of love, ambition, and duplicity, set against the storied seascape of Newport, Rhode Island A reckless wager between a tennis pro with a fading career and a drunken party guest--the stakes are an antique motorcycle and an heiress's diamond necklace--launches a narrative odyssey that braids together three centuries of aspiration and adversity. A witty and urbane bachelor of the Gilded Age embarks on a high-risk scheme to marry into a fortune; a young writer soon to make his mark turns himself to his craft with harrowing social consequences; an aristocratic British officer during the American Revolution carries on a courtship that leads to murder; and, in Newport's earliest days, a tragically orphaned Quaker girl imagines a way forward for herself and the slave girl she has inherited. In The Maze at Windermere Gregory Blake Smith weaves these intersecting worlds into a brilliant tapestry, charting a voyage across the ages into the maze of the human heart"--
Keywords: FICTION / Historical; FICTION / Sagas; FICTION / Literary